The role of legumes in farming systems of sub-Saharan Africa - Tothill, J.C. (International Livestock Centre for Africa, 1986)
Discusses the role of legumes in the farming systems of sub-Saharan Africa and the existing farming systems in two agroclimatic zones, viz, humid and semi-arid, and Sudano-Sahelian zone; also discusses factors affecting management.